The Use of Sociolect in the Nuwewang Village Community - Sairmaly, Rogers; Sasabone, Carolina; Tabelessy, Novita (Universitas Pattimura, 2025)
Sociolect is a highly debated subject that necessitates much time for discussion. Sociolect refers to the linguistic variation employed by a specific social group. This research study is about the use of sociolects in the Nuwewang Village community, Letti District, Southwest Maluku Regency. The purpose of this study is to describe the use of sociolects in the Nuwewang Village community, Letti District, Southwest Maluku Regency. The data collection techniques used in this study are observation techniques, interviews, recordings and field notes. The data analysis techniques of this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are four types of sociolects consisting of fifteen vulgar language data, five slang language data, twenty-five colloquial languages, and twelve jargon language data.